Total Correction of Tetralogy of Fallot After Percutaneous Coiling of MAPCA: A Case Report - Rasul, GH; Sharifuzzaman, M; Hassan, M; Rahman, MZ; Momenuzzaman, M; Kabir, J (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v32i1.6010 Bangladesh Journal of Child Health 2008; Vol.32(1): 29-32